2012
DOI: 10.1159/000338520
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Metastases of an Endometrial Stromal Sarcoma: Report of the First Case

Abstract: Background: Endometrial stromal sarcomas (ESSs) of the uterus are rare gynecological malignancies. Common locations of distant metastases are vagina, vulva, lung, mediastinum, abdomen, bones and ovaries. Case Report: We present the case of a 69-year-old woman with a Federation of Gynecology and Obstetrics (FIGO) IIb (classification 2009) ESS of the uterus of high-grade malignancy. Initially, a hysterectomy Piver II and total colpectomy were performed, followed by pelvic field irradiation. 8 months later, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In our study, the most common histotypes were in agreement with the previous results. Furthermore, we also found some cases of rare sarcoma subtypes, including glomus tumor, endometrial stromal sarcoma and phyllodes tumor, for which there are case reports of brain metastases [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the most common histotypes were in agreement with the previous results. Furthermore, we also found some cases of rare sarcoma subtypes, including glomus tumor, endometrial stromal sarcoma and phyllodes tumor, for which there are case reports of brain metastases [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Cranial metastasis of endometrial stromal sarcoma has been reported 4 times by different authors until now. One case had metastasis in the sphenoid bone and lumbar spine [14], another case had lung and cerebral metastasis [15], and the third case had multiple cerebral metastases [16]. The last case has been recently reported in 2013, and the patient in this case had a lesion mimicking meningioma and located at right occipital lobe [17].…”
Section: Discussionmentioning
confidence: 85%
“…The current case did not give any history related to her genital tract and she had been presented due to respiratory symptoms.Common locations of distant metastases are the vagina, vulva, lung, mediastinum, abdomen, bones and ovaries 9. There are small cases of unusual metastatic sites in patients with ESS such as the brain,10 heart,11 stomach12 and sigmoid colon 13. Butwhat distinguishes this case is the fact that pulmonary metastases was the initial presentation of ESS, the patient had a history of breast carcinoma andimmunoreactivity to CD10 was not found.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, ESS is a genetically heterogeneous group of uterine sarcomas, of which almost half are associated with JAZF1 rearrangement. Lee et al 16 recently identified a novel genetic fusion between YWHAE and FAM22A/B in ESS harbouring t10 17 (q22;p13). They described the histological and IHC features for YWHAE-FAM22 ESS.…”
Section: Discussionmentioning
confidence: 99%